The story and language of heraldry the development of coats of arms and heraldic symbols, with 575 illustrations - Slater, Stephen (Southwater, an imprint of Anness Publishing Ltd., 2012)
An essential introduction to understanding and interpreting heraldry for novices, as well as a must-have source book and reference manual for experts. Accessible and contemporary in style, the book brings new life to the subject, with a clear text revealing why heraldry remains a treasured part of our heritage